2018
DOI: 10.1021/acs.energyfuels.8b00324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asphaltene Characteristics on Its Solubility and Overall Stability

Abstract: Complex molecular structure, high impurity content, and self-association tendency of asphaltenes make the determination of their phase behavior very difficult. Because asphaltene phase behavior is indicative of asphaltene stability within the bulk oil, it is very important to understand its stability. Various production and flow assurance challenges related to precipitation of unstable asphaltenes can be prevented by proper comprehension of asphaltene stability. This study provides a data set on 11 different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The SARA value determined from different techniques could show significant difference in values for the same oil, therefore, may result in inaccurate stability predictions from these models (Pereira et al 2017;Kharrat et al 2007;Fan et al 2002). Furthermore, these predicting models do not take into account the factors like operational parameters such as pressure and temperature, solubility parameter of crude oil and asphaltene, polarities of resins and asphaltenes and compositional and structural characteristics of asphaltene molecule which according to previous studies play a major role in deciding the asphaltenes stability in crude oil (Gharbi et al 2017;Guzmán et al 2017;Ali et al 2021b;Punase et al 2016;Prakoso et al 2015Prakoso et al , 2018Goual and Firoozabadi 2002;Hascakir 2017;Asomaning 2003). Finally, the collection point for the testing of crude oil is also important because these SARA values may differ with respect to location due to the compositional changes occurring in crude oil during production.…”
Section: Resultsmentioning
confidence: 99%
“…The SARA value determined from different techniques could show significant difference in values for the same oil, therefore, may result in inaccurate stability predictions from these models (Pereira et al 2017;Kharrat et al 2007;Fan et al 2002). Furthermore, these predicting models do not take into account the factors like operational parameters such as pressure and temperature, solubility parameter of crude oil and asphaltene, polarities of resins and asphaltenes and compositional and structural characteristics of asphaltene molecule which according to previous studies play a major role in deciding the asphaltenes stability in crude oil (Gharbi et al 2017;Guzmán et al 2017;Ali et al 2021b;Punase et al 2016;Prakoso et al 2015Prakoso et al , 2018Goual and Firoozabadi 2002;Hascakir 2017;Asomaning 2003). Finally, the collection point for the testing of crude oil is also important because these SARA values may differ with respect to location due to the compositional changes occurring in crude oil during production.…”
Section: Resultsmentioning
confidence: 99%
“… 1 The fourth way to judge asphaltene stability in crude oil is through asphaltene compositional and structural characteristics. Previous studies reported that the H/C ratio of asphaltene, 1 asphaltene solubility profile distribution, 51 , 53 asphaltene aromaticity and density, 52 polarity of asphaltene, 54 , 57 , 58 and electrical charges on asphaltenes 59 can provide information regarding the chance for asphaltene stability in crude oils. However, this method required the extracted asphaltene sample, which may lead to uncertainties in results due to asphaltene extraction methodology applied and the absence of the effect of other crude oil components such as resins, aromatics, and saturates.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 22 , 23 However, because of the molecular imbalance and the impurity content of saturate and aromatic fractions, it has recently been found that they may have also polarity. 24 Resins are known as polar fraction of the crude oil, which is soluble in lower molecular weight n -alkanes and contains less amount of metals as compared to asphaltenes. 25 , 26 Asphaltenes are the most polar and the heaviest fraction of crude oil and are insoluble in lower molecular weight n -alkanes and soluble in aromatic solvents; they contain NSO and heavy metals in their molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 11 However, for the heavy oil reservoirs, not only reservoir rocks but also asphaltenes are charged because of interactions of asphaltenes with reservoir rock. 24 , 30 , 31 Thus, in heavy oil reservoirs, the reservoir rock particles may physically be attached to asphaltene clusters and make the asphaltene surfaces charged. 20 , 32 Although this interaction is physical and not chemical, since this interaction is in micro- and nanoscales, it is irreversible.…”
Section: Introductionmentioning
confidence: 99%